Kolekcja sztuki XX w. : w Muzeum Sztuki w Lodzi. - Muzeum Sztuki, Łódź (Warszawa : Galeria Zacheta, 1991)
Abakanowicz, Magdalena ; Adler, Jankiel ; Arp, Hans/Jean ; Baertling, Olle ; Baj, Enrico ; Baljeu, Joost ; Balka, Miroslaw ; Baranow, Leonid ; Baumeister, Willi ; Beuys, Joseph ; Bruszewski, Wojciech ; Chlanda, Marek ; Davis, Douglas ; Feininger, Lyonel ; Grabowski, Stanislaw ; etc.
Kolekcja : w Muzeum Sztuki w Lodzi, Galeria Zacheta, Warszawa, 6.V. - 2.VI.1991
Pools
kunstcatalogus